2014
DOI: 10.1177/1078087414530545
|View full text |Cite
|
Sign up to set email alerts
|

Cities and Sustainability

Abstract: Polycentric theory, as applied to sustainability policy adoption, contends that municipalities will act independently to provide public services that protect the environment. Our multilevel regression analysis of survey responses from 1,497 municipalities across the United States challenges that notion. We find that internal drivers of municipal action are insufficient. Lower policy adoption is explained by capacity constraints. More policymaking occurs in states with a multilevel governance framework supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(50 citation statements)
references
References 85 publications
(126 reference statements)
4
44
1
1
Order By: Relevance
“…Our results show that the total population size exerts a positive influence in this respect, which is in line with the findings of previous authors [16,82]. In contrast to previous results [59], we found that the dependent population has no influence on LG transparency on sustainability.…”
Section: Second Regression Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…Our results show that the total population size exerts a positive influence in this respect, which is in line with the findings of previous authors [16,82]. In contrast to previous results [59], we found that the dependent population has no influence on LG transparency on sustainability.…”
Section: Second Regression Analysissupporting
confidence: 92%
“…In contrast to previous results [59], we found that the dependent population has no influence on LG transparency on sustainability. Moreover, while previous studies have found evidence of a positive influence of population density, our own analysis revealed no such relation with sustainability transparency [82]. Finally, corroborating previous studies [13,16,59,82], we found no evidence of any association between the size of the immigrant population and the disclosure of sustainability information.…”
Section: Second Regression Analysissupporting
confidence: 87%
See 3 more Smart Citations